2015
DOI: 10.12681/sas.822
|View full text |Cite
|
Sign up to set email alerts
|

The Kosovo trauma in Serbian national narratives

Abstract: Η εργασία αυτή αναψηλαφεί τις διαφορετικές σερβικές ερμηνείες ίου Τραύματος του Κοσσυφοπεδίου από την περίοδο της σέρβικης ανεξαρτησίας μέχρι σήμερα. Επικεντρώνεται στις διαφορετικές ερμηνείες οι οποίες χρησιμοποιούν τον θρύλο ως σημείο αναφοράς για να προσδώσουν σε αυτόν πολιτικές και πολιτισμικές διαστάσεις που συμβαδίζουν με τις ανάγκες κάθε εποχής. Η αποκρυστάλλωση του μύθου είναι ταυτόχρονη με τη διαδικασία συγκρότησης του νεότερου σερβικού κράτους. Επιπλέον, ιδιαίτερη έμφαση δίνεται στις μετά το 1980 ερμ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
1
Order By: Relevance
“…26-29). Ivana Spasić wskazuje jednak, że trauma związana z Kosowem nie tkwi "w Serbach", ale w tym, co pomiędzy nimi, a co przybiera charakter przestrzeni dyskursywnej (Spasić, 2011(Spasić, , s. 99, za: Čolović, 2019. Dyskursywność w tym wypadku tworzy się na skutek konieczności wyboru pomiędzy dwiema wiedzami: Człowiek-Serb uznaje traumę kosowską albo Człowiek-Serb odrzuca traumę kosowską.…”
Section: Pogranicze Jako Ziemia Traumatogennaunclassified
“…26-29). Ivana Spasić wskazuje jednak, że trauma związana z Kosowem nie tkwi "w Serbach", ale w tym, co pomiędzy nimi, a co przybiera charakter przestrzeni dyskursywnej (Spasić, 2011(Spasić, , s. 99, za: Čolović, 2019. Dyskursywność w tym wypadku tworzy się na skutek konieczności wyboru pomiędzy dwiema wiedzami: Człowiek-Serb uznaje traumę kosowską albo Człowiek-Serb odrzuca traumę kosowską.…”
Section: Pogranicze Jako Ziemia Traumatogennaunclassified
“…A range of empirical studies have demonstrated how cultural traumas influence national identity through events including war and genocide (Alexander 2004b; Alexander and Gao ; Bartmański and Eyerman ; Geisen ; Spasić ), terrorism (Smelser 2004b), the end of communism (Sztompka ) and even the destruction of objects (Debs ). Yet theorists have only briefly considered what function trauma narratives play in society, with widely varying explanations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Sztompka stresses the unifying power of a cultural trauma as ‘a force for social becoming’ (: 194), and Alexander and Gao argue that traumas function, ‘not only as threats to already existing collective identity, but as symbolic vehicles that allow future collective identities to be formed’ (2011: 1010). Spasić's examination of the importance of the fourteenth‐century Battle of Kosovo in nineteenth‐century Serbia demonstrates the range of functions played by one myth: ‘an inspiration, a call to arms, a spiritual reminder, an emotional bond with their fellows, or a scourge to chastise them’ (2011: 87). The variety of explanations creates a conundrum: why does the collective remembrance of a traumatic event result in such diversity of outcomes?…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations